A pandemia de COVID-19: os conflitos maritais e a ética no direito brasileiro - Ikeda, Marcio Hiroshi (2023)
This research analyzes and outlines the set of values and principles that led people through the difficulties encountered in the covid 19 pandemic. Then he starts to appreciate the conflicts and the familiar strangers studying the immovable ethics, which should not change, in an atypical crisis situation. Then, it proposes an analysis of the philosophical, ethical, scientific and religious levels, seeking to understand the experiential system and the set of norms and customs that society understands as correct. Thus, methodologically, I focus on a robust theoretical framework of national and international authors and of these, three stand out, Thomas Hobbes, Jean-Jacques Rousseau and Immanuel Kant. Next, we analyze interpersonal relationships, the spread of false news, the cult of reason in marital problems and the dilemmas they face. The study emphasizes the true feelings that emerged during the pandemic and the isolation crisis, understanding the human heritage and integrity consistent with the social development of present and future generations. Through this tragedy, it seeks to understand the moral values that vary in time and space